2015
DOI: 10.4314/ejhs.v25i4.14
|View full text |Cite
|
Sign up to set email alerts
|

CASE REPORT Leiomyoma Arising from Mullerian Remnant, Mimicking Ovarian Tumor in a Woman with MRKH Syndrome and Unilateral Renal Agenesis

Abstract: BACKGROUND: Leiomyoma with secondary changes arising from Mullerian remnant may mimic ovarian tumor in women with Mayer-Rockitansky-Kuster-Hauser (MRKH) syndrome in patients with pelvic mass and urologic abnormalities. CASE DETAIL: The patient was a 40 years old known case of MRKH, presented with lower abdominal pain and swelling for over one year. On physical examination, large pelvic mass (about 15cm by 10cm) was found and a diagnosis of ovarian tumor was made by imaging which also showed absent right kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…[1][2][3][4][5][6][11][12][13] Differential diagnosis of leiomyoma of rudimentary uterus in MRKH syndrome includes ovarian fibroma, gastrointestinal stromal tumor (GIST) of intestine and extravesical leiomyoma of urinary bladder. The uncommon occurrence of leiomyoma in MRKH may be explained by decreased concentration or sensitivity of estrogen receptors in the rudimentary tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][11][12][13] Differential diagnosis of leiomyoma of rudimentary uterus in MRKH syndrome includes ovarian fibroma, gastrointestinal stromal tumor (GIST) of intestine and extravesical leiomyoma of urinary bladder. The uncommon occurrence of leiomyoma in MRKH may be explained by decreased concentration or sensitivity of estrogen receptors in the rudimentary tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of congenital uterine anomalies appears to be 6.7% in fertile population, and it is found in 7.3% of an infertile population. 1 Occurrence of a myoma arising from a mullerian remnant is an extremely rare finding and only few cases reported in literatures. [1][2][3][4][5][6] The incidence of associated urologic abnormalities ranges between 15-40%, and skeletal anomalies such as congenital fusion or absence of vertebra occur in approximately 12-50% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…In the most recent publications on MRKH syndrome, we could find cases reported on leiomyoma, adenomyosis, but ovarian tumor is rare in MRKH syndrome and difficult to diagnose if it is not bulky. [11][12][13][14] The incidence of the combination of MRKH with ovarian tumors was not reported. However, a review of the literature demonstrated nearly a dozen reported cases of MRKH syndrome associated with ovarian tumors (Table 1).…”
Section: Diagnosismentioning
confidence: 99%
“…These patients are characterized by a normal female karyotype, secondary sexual characteristics, and ovarian function [2]. As ovarian function is normal in most patients with MRKH syndrome, the development of estrogen-dependent pathologies, such as leiomyomas and adenomyosis, is possible in the rudimentary uterine horn [3,4] or in other pelvic areas [5]. Here, we report a case with severe abdominal pain that was diagnosed as torsion of a right rudimentary uterine horn with multiple leiomyomas in a patient with MRKH syndrome.…”
Section: Introductionmentioning
confidence: 99%